Accurate measurement of effective Li–Li scalar coupling constants: the NMR missing link for alkyllithium aggregates. Issue 99 (27th November 2020) - Hedouin, Matthieu; Harrison-Marchand, Anne; Maddaluno, Jacques; Oulyadi, Hassan
Abstract : Alkyllitium mixed aggregates: dynamics-free value of the 2 J Li–Li as a simple access to various structural factors, including the dynamics, solvation and the steric hindrance of alkyl chains. Abstract : Scalar coupling in organolithium systems can provide access to useful structural and dynamic informations. In this work, we propose a robust method for the accurate measurement of the effective 2 J Li–Li coupling constant in tetramerics alkyllithium aggregates. This crucial information, unavalaible to date, gives a simple access to various structural factors, including the dynamics, solvation and the operative steric hindrance of alkyl chains.